Economic analysis and policy in underdeveloped countries - Bauer, P.T. (London, 1957)
CONCERN WITH THE problems of underdeveloped countries is most ancient. It manifests itself when ever some countries are considerably more advanced than others and are recognized as being so, whether on military or economic or yet other grounds. The main centers of Hellenistic culture were so recognized and, later, Imperial Rome, her successor, Byzantium, and Byzantium's flourishing city-state neighbours. Subsequently, with the discovery of the New World and the establishment of effective mari time communication with America and with south and east Asia, northern and western Europe were deemed to hold the relatively most advanced states, together with the most progressive ways of producing and distributing goods. It was principally from them that men and capital and advanced ways of doing things flowed abroad, especially to the New World.
Keywords: Underdeveloped countries economic conditions